2019
DOI: 10.1007/s11606-019-05549-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Opioid and Benzodiazepine Use in Opioid-Naïve Patients with Newly Diagnosed Low Back and Lower Extremity Pain

Abstract: BACKGROUND: The morbidity and mortality associated with opioid and benzodiazepine co-prescription is a pressing national concern. Little is known about patterns of opioid and benzodiazepine use in patients with acute low back pain or lower extremity pain. OBJECTIVE: To characterize patterns of opioid and benzodiazepine prescribing among opioid-naïve, newly diagnosed low back pain (LBP) or lower extremity pain (LEP) patients and to investigate the relationship between benzodiazepine prescribing and long-term op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Despite the questionable effect of opioids in acute LBP 21 and the evidence of poorer outcomes compared to non-opioid treatments, 22,23 opioids are still frequently prescribed for patients with LBP. 5,[24][25][26] In our study 34% of all patients received an opioid. Comparing this percentage of opioid use to the sparse national comparative data, 20 we found that the percentage in our study was almost twice as high.…”
Section: Opioid Pain Medication Therapiesmentioning
confidence: 60%
“…Despite the questionable effect of opioids in acute LBP 21 and the evidence of poorer outcomes compared to non-opioid treatments, 22,23 opioids are still frequently prescribed for patients with LBP. 5,[24][25][26] In our study 34% of all patients received an opioid. Comparing this percentage of opioid use to the sparse national comparative data, 20 we found that the percentage in our study was almost twice as high.…”
Section: Opioid Pain Medication Therapiesmentioning
confidence: 60%
“…We found that 70.9% of new persistent opioid users lled a sedative-hypnotic prescription during the study period as well, while 98.2% of new persistent sedativehypnotic users lled an opioid prescription. Sedative-hypnotics are known to potentiate the respiratory depressive effects of opioids [33], and concomitant opioid and sedative-hypnotic use has been associated with increased rates of long-term opioid use, opioid overdose and all-cause mortality [34][35][36][37]. In particular, pre-operative sedative-hypnotic use among opioid-naïve patients increases the risk of long-term opioid use post-operatively [38].…”
Section: Discussionmentioning
confidence: 99%
“…We found that 70.9% of new persistent opioid users lled a sedative-hypnotic prescription during the study period as well, while 98.2% of new persistent sedativehypnotic users lled an opioid prescription. Sedative-hypnotics are known to potentiate the respiratory depressive effects of opioids [33], and concomitant opioid and sedative-hypnotic use has been associated with increased rates of long-term opioid use, opioid overdose and all-cause mortality [34][35][36][37]. In particular, pre-operative sedative-hypnotic use among opioid-naïve patients increases the risk of long-term opioid use post-operatively [38].…”
Section: Discussionmentioning
confidence: 99%